Heteroatom Modified Hybrid Carbon Quantum Dots Derived from Cucurbita pepo for the Visible Light Driven Photocatalytic Dye Degradation - Smrithi, S. P.; Kottam, Nagaraju; Vergis, Bincy Rose (Topics in catalysis, 2025)
Zero dimensional nanocarbon dots with unique photophysical and optical characters have grabbed tremendous popularity owing to its application in diverse fields such as sensing, bioimaging, catalysis and energy harvesting. Herein, we report the green synthesis of nitrogen modified carbon dots (NCQDs) from the extract of Cucurbita pepo via hydrothermal technique. The structural, morphological and optical characterizations of the as synthesized NCQDs were carried out using X-ray diffraction studies, Scanning electron microscopy, Energy dispersive X-ray spectroscopy, High resolution transmission electron microscopy (HR-TEM), UV–Visible absorption Spectroscopy, Photoluminescence (PL) Spectroscopy and Fourier transform infrared spectroscopy (FT-IR). The fluorescence quantum yield of the developed NCQDs were found to be 12.19% and the PL spectra appeared to exhibit typical excitation dependent emission behavior of carbon quantum dots. The intrinsic visible light driven photocatalytic activities of NCQDs were studied using crystal violet (CV) dye as the model pollutant. The evaluation of the photocatalytic activity of NCQDs resulted in achieving 99.9% CV dye degradation in 180 min in the presence of 1 mL H 2 O 2 . The advantages of efficient visible light absorption coined with the generation of semiconducting localized states owing to the presence of surface functionalities and electron transfer properties of NCQDs have played prominent roles in the obtained results. Radical trapping experiment revealed the prominent role played by the ⋅ OH radical and the fitting of Langmuir–Hinshelwood kinetic approach yielded an apparent rate constant value of 0.02581 min −1 . Since the photocatalytic activity exhibited by biogenic NCQDs are comparable with those reported with the metal based photocatalysts, this study casts light on the development of alternative metal-free photocatalytic approach for organic pollutant degradation and environmental conservation.